Functional nano-systems for transdermal drug delivery and skin therapy. Issue 6 (24th February 2023) - Liu, Lijun; Zhao, Wenbin; Ma, Qingming; Gao, Yang; Wang, Weijiang; Zhang, Xuan; Dong, Yunxia; Zhang, Tingting; Liang, Yan; Han, Shangcong; Cao, Jie; Wang, Xinyu; et al.
Abstract : Functional nano-systems have been applied as a promising strategy for transdermal drug delivery and skin therapy. Abstract : Transdermal drug delivery is one of the least intrusive and patient-friendly ways for therapeutic agent administration. Recently, functional nano-systems have been demonstrated as one of the most promising strategies to treat skin diseases by improving drug penetration across the skin barrier and achieving therapeutically effective drug concentrations in the target cutaneous tissues. Here, a brief review of functional nano-systems for promoting transdermal drug delivery is presented. The fundamentals of transdermal delivery, including skin biology and penetration routes, are introduced. The characteristics of functional nano-systems for facilitating transdermal drug delivery are elucidated. Moreover, the fabrication of various types of functional transdermal nano-systems is systematically presented. Multiple techniques for evaluating the transdermal capacities of nano-systems are illustrated. Finally, the advances in the applications of functional transdermal nano-systems for treating different skin diseases are summarized.